Analysing the Spiritual Effects of Emotional Freedom Technology (SEFT) in Building Psychological Well-being: Systematic Literature Review - Rachmawardany, Devani Widya; Mustikawati, Irma Finurina; Septianawati, Paramita; Immanuel, Glorio (Syntax Corporation Indonesia, 2024)
Spiritual emotional freedom techniques (SEFT) influence psychological well-being because psychological well-being is an individual's ability to prosper with all one's abilities and weaknesses cope with life's stresses, can work productively and fruitfully. The method used is a systematic literature review by collecting various literature, namely Scopus, and PubMed. Using SEFT keywords; psychological well-being, effects. The results of several studies indicate that there is an influence of SEFT in developing psychological well-being. SEFT is carried out with the power of prayer and tapping at several points will influence the level of stress. SEFT therapy can be applied in the field of clinical practice to support patient care.